Design and Development of an Android-Based Urban Air Quality Monitoring System (Journal of Advanced and Applied Science and Technology, 2025)
The advancement of transportation technology has redefined the concept of distance and enabled intercontinental travel within a short time, an achievement that was almost unattainable a century ago. While these developments offer convenience and efficiency, they also pose significant environmental challenges, particularly air pollution caused by vehicle emissions, which has become an increasingly urgent global issue. Additionally, noise and humidity problems also affect public health, especially in tropical regions such as Indonesia. With growing awareness of environmental issues, This study aims to design an Internet of Things based air quality monitoring system, temperature, and noise levels. The system is expected to provide real-time reports on environmental conditions, enabling users to access crucial information with ease. By implementing this technology, it is hoped that efforts to mitigate pollution and improve the quality of life can be carried out effectively. The method employed in this study integrates hardware and application development. The findings indicate that the software-processed data can be managed using the Air Quality application, enabling real-time visualization through graphs or circular bar charts.